2018
DOI: 10.1093/annonc/mdy037
|View full text |Cite
|
Sign up to set email alerts
|

Expression III: patients’ expectations and preferences regarding physician–patient relationship and clinical management—results of the international NOGGO/ENGOT-ov4-GCIG study in 1830 ovarian cancer patients from European countries

Abstract: This study underlines the high need of patients with ovarian cancer for all details concerning treatment options irrespective of their cultural background, the stage of disease and the patient's age. Increased information requirements regarding potential side effects and treatment alternatives were recorded. Besides the need for more effective therapy, alopecia and fatigue are the most important side effects of concern to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 24 publications
1
24
0
1
Order By: Relevance
“…Younger patients in our study had higher expectations of full recovery. Concordant with the results of our European Expression III survey, including 1830 patients with primary and relapsed ovarian cancer, a significant number of patients expected complete response from maintenance therapy, even patients with recurrent disease 11. These results show that there is still a gap between the efficacy of maintenance therapy and patients' expectations.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Younger patients in our study had higher expectations of full recovery. Concordant with the results of our European Expression III survey, including 1830 patients with primary and relapsed ovarian cancer, a significant number of patients expected complete response from maintenance therapy, even patients with recurrent disease 11. These results show that there is still a gap between the efficacy of maintenance therapy and patients' expectations.…”
Section: Discussionsupporting
confidence: 82%
“…In an interdisciplinary workshop with gynecologists, oncologists, statisticians, psychologists, nurses, and representatives of self-help organizations, the survey was implemented. Different studies on the topic were used as a basis for discussion and the questionnaire 11 12. The questions were answered as multiple choice, free text, or on a scale of 1–10.…”
Section: Methodsmentioning
confidence: 99%
“…A number of published cross-national research focus on a specific type of cancer. Two most recent and comprehensive studies in this area, The ‘Every Woman’ study supported by the World Ovarian Cancer Coalition completed a study in 2018 by surveying 1531 women in 44 countries, and incorporated attitudes and practices in its scope;11 and Expression III: patients’ expectations and preferences regarding the physician–patient relationship and clinical management6 also reports data from 1830 patients in European countries, and both look at only ovarian cancer patients. Therefore, even though they provide an important comparison for ovarian cancer patient data, the scope of this survey extends beyond their focus covering all gynecological cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Yet we found that only an average of 31.1% of patients received any printed materials from their healthcare providers. Cancer patients have high levels of unmet needs and prefer receiving more information and support for their disease6 20 21 with a strong preference in being involved in the decision-making process of their treatments 22–24. This can only be efficient by a matching increase in support and educational services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation